Aerodynamic performance of X-plane with two different types of inboard stores - A Rahman, Mahadhir; Yazdi Harmin, Mohammad; Fuad Koslan, Mohd; Rashdan Saad, Mohd; Faisal Abdul Hamid, Mohd (International Journal of Engineering and Technology, 2018)
This paper presents the investigation of aerodynamic performance of inboard Store-X and Store-Y configurations on the X-plane aircraft model through computational fluid dynamics (CFD) analysis. The X-plane and Store-Y represent the default store and pylon integration while Store-X provides a possibility for other types of store to be integrated. These stores are loosely based upon the two most commonly used by the western and eastern blocks. The resultant lift, drag and moment forces are of interest in order to observe their impact with respect to the two different stores configurations. The finding shows that the aerodynamic impact with respect to Store-X installation on the inboard pylon station is insignificant when compared to default system, hence offers the safety of delivering the Store-X from the X-plane aircraft.